Clinical Characteristics of Rhabdomyosarcoma in Children: A 4-Year Study in a Tertiary Hospital - Lelani Reniarti; Nur Fatharani; Nur Suryawan (Althea Medical Journal, 2020)
Background: Rhabdomyosarcoma (RMS) is the most common soft-tissue sarcomas (STS) in children. Even though the survival rate has increased, the mortality rates remain significantly higher in developing countries due to delay in diagnosis contributed by its diverse and clinical manifestations. This study aimed to describe the clinical characteristics of RMS patients at the Department of Child Health, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia.Methods: A descriptive cross-sectional retrospective study was conducted using a total sampling method on medical records of RMS patients aged ≤ 18-year-old during a 4-year period (2015-2018). Data on patient demographics, clinical manifestations, biopsy procedure, histopathological subtype, tumor size, primary site, pre-treatment staging, and treatment were reviewed and presented.Results: Of 30 data retrieved, male (57%), aged 1 to 5-year-old (47%), and diagnosed through open biopsy (63%) comprised the majority of the patients. More than half of the patients came with advanced stage of the disease (80%) and were treated with chemotherapy (83%). Most RMS patients had a tumor located in the head and neck region (40%) with a size of >5 cm (70%) and embryonal subtypes (43%). The remaining patients experienced alveolar subtype (17%), spindle cell subtype (13%), and unknown subtype (27%) of RMS.Conclusion: Children with a tumor in the head and neck region should be suspected as rhabdomyosarcoma, as there are various clinical characteristics of RMS in children found in this study.